2020
DOI: 10.2147/copd.s249409
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mid-Term Effects of Pulmonary Rehabilitation on Cognitive Function in People with Severe Chronic Obstructive Pulmonary Disease</p>

Abstract: Purpose: Cognitive dysfunction is a common impairment associated with COPD. However, little is known about 1) its prevalence among those subjects referred for pulmonary rehabilitation (PR), 2) how it may affect the benefit of PR, 3) whether PR improves cognitive function and 4) whether cognitive dysfunction affects the usability of telehealth technology usually used to deliver in-home PR. Patients and Methods: Fifty-six subjects with stable COPD (54% females, mean age 62 years (SD 9) and median FEV 1 0.9 L (IQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 56 publications
6
34
0
Order By: Relevance
“…Although we saw no improvement in cognition for the whole PR group, our results are in line with Bonnevie et al [25] who found cognitive improvements following PR in people with COPD and CI. Previous studies investigated the effect of more intensive PR programmes, such as a 3-week in-patient programme (5-6 sessions/week) [23] or an 8-week programme (3 sessions/week) [25]. We have been able to observe the same cognitive changes in people with COPD and CI following a less intensive PR programme.…”
Section: Pulmonary Rehabilitation In People With Stable Copd Symptomssupporting
confidence: 92%
See 3 more Smart Citations
“…Although we saw no improvement in cognition for the whole PR group, our results are in line with Bonnevie et al [25] who found cognitive improvements following PR in people with COPD and CI. Previous studies investigated the effect of more intensive PR programmes, such as a 3-week in-patient programme (5-6 sessions/week) [23] or an 8-week programme (3 sessions/week) [25]. We have been able to observe the same cognitive changes in people with COPD and CI following a less intensive PR programme.…”
Section: Pulmonary Rehabilitation In People With Stable Copd Symptomssupporting
confidence: 92%
“…PR has many benefits for people living with COPD [19], and more recently studies have demonstrated the positive effects of PR on cognitive status using the MoCA [23,25]. Although we saw no improvement in cognition for the whole PR group, our results are in line with Bonnevie et al [25] who found cognitive improvements following PR in people with COPD and CI.…”
Section: Pulmonary Rehabilitation In People With Stable Copd Symptomssupporting
confidence: 88%
See 2 more Smart Citations
“…Eleven articles included validity, 29 , 31 40 seven articles included reliability, 30 , 31 , 33 , 35 , 41 43 13 articles included responsiveness, 36 , 37 , 43 53 and five articles included interpretability 33 , 34 , 37 , 54 , 55 of the step tests. Details on each article included in this review are presented in Supplemental Appendix 3.…”
Section: Resultsmentioning
confidence: 99%